O consumidor e a garantia do acesso à justiça: avaliação da política nacional das relações de consumo com amparo na experiência do PROCON Câmara Municipal de Sobral-CE - Alves, Juliana Freitas (2022)
This research deals with the evaluation of the National Policy for Consumer Relations - PNRC in the Municipality of Sobral, based on the experience of PROCON implemented within the scope of this Legislative House, observing its contribution as a facilitating mechanism for consumers in resolving consumerist conflicts and, from this, verifying to what extent it promotes access to justice. The evaluative model chosen for this work is the evaluative research (SILVA, 2008), which understands the evaluation of public policies from two perspectives that dialogue between the technical and the political. Then, in the light of a bibliographic and documentary analysis, we developed the theoretical framework, addressing the themes of consumer society, consumer rights, access to justice and fundamental aspects of the PNRC. The research has a quantitative and qualitative approach. The main data collection techniques adopted were the application of questionnaires with the beneficiaries of the policy (consumers) and semi-structured interviews with the public agents responsible for the implementation of the PNRC at PROCON, enabling the understanding of the social reality in which the policy put under analysis is developed. The temporal space taken for the study goes from 2017 to 2019. The data collected in the questionnaires were analyzed through descriptive statistical analysis in the light of the theoretical framework. To analyze the information obtained through the semi-structured interviews, Bardin's content analysis technique was used. The results showed that PROCON Sobral City Hall contributes significantly as a facilitating mechanism for resolving consumerist conflicts, in an alternative and extrajudicial manner, promoting real access to justice in the municipality of Sobral. It was also verified that PROCON Câmara Municipal of Sobral, as a member of the National System of Consumer Defense - SNDC, guarantees not only access to justice for consumers, but also establishes a change of paradigm for a more democratic, just, egalitarian and humanitarian access to justice. The results of PROCON Câmara demonstrate its protagonism in the achievement and promotion of consumer defense. There have been advances, however, still very incipient and permeated by complex challenges and obstacles to be corrected within the Municipal Chambers throughout the country, among them, fragility and ease for the dismantling of the policy, disarticulation with SNDC and with other public apparatuses, change in presidential management. Thus, it is intended to offer to the academia a contribution about new openings, paths and perspectives of access to justice for consumers, which is not simply reduced to the Judiciary, but a real and broad access of resolution of conflicts involving consumers, as is the case of the alternative way of PROCON City Council of Sobral.